Graphite/epoxy-coated flaky FeSiCr powders with enhanced microwave absorption - Zhang, Haonan (2024)
Flake-shaped FeSiCr (FFSC) material is expected to be a promising microwave absorbent due to its excellent magnetic properties and environmental resistance. By introducing carbon-based materials through suitable coatings, the electromagnetic parameters and energy loss can be tuned to improve the performance of FFSC. A facile solution-blending method was deployed to prepare graphite- and epoxy resin-encapsulated FFSC (FFSC@G/E) powders with a core–shell structure. FFSC@G2000/E showed excellent performance in the X band (8–12 GHz), a minimum reflection loss (RLmin) of −42.77 dB at a thickness of 3 mm and a maximum effective absorption bandwidth (EABmax, RL < −10 dB) that reached 4.55 GHz at a thickness of 2.7 mm. This work provides a route for the production of novel high-performance microwave absorbers.